Abundance and diversity of eukaryotic rather than bacterial community relate closely to the trophic level of urban lakes. (23rd December 2022) - Wan, Wenjie; Gadd, Geoffrey Michael; He, Donglan; Liu, Wenzhi; Xiong, Xiang; Ye, Luping; Cheng, Yarui; Yang, Yuyi
Abstract: Scientific understanding of biotic effects on the water trophic level is lacking for urban lakes during algal bloom development stage. Based on the Illumina MiSeq sequencing, quantitative polymerase chain reaction (PCR), and multiple statistical analyses, we estimated distribution patterns and ecological roles of planktonic bacteria and eukaryotes in urban lakes during algal bloom development stage (i.e., April, May, and June). Cyanobacteria and Chlorophyta mainly dominated algal blooms. Bacteria exhibited significantly higher absolute abundance and community diversity than eukaryotes, whereas abundance and diversity of eukaryotic rather than bacterial community relate closely to the water trophic level. Multinutrient cycling (MNC) index was significantly correlated with eukaryotic diversity rather than bacterial diversity. Stronger species replacement, broader environmental breadth, and stronger phylogenetic signal were found for eukaryotic community than for bacterial community. In contrast, bacterial community displayed stronger community stability and environmental constraint than eukaryotic community. Stochastic and differentiating processes contributed more to community assemblies of bacteria and eukaryotes. Our results emphasized that a strong linkage between planktonic diversity and MNC ensured a close relationship between planktonic diversity and the water trophic level of urban lakes. Our findings could be useful to guide the formulation and implementation of environmental lake protection measures.